Testing The Effectiveness of An Ethanol Extract Gel Preparation of Kelakai Leaves (Stenochlaena palustris (Burm.F.) Bedd.) on Reducing The Extent of Burns in Male White Rats (Rattus novergicus) - Syarifuddin, Aminah; Novandi Purba; Yayuk Rahayu Suyudi; Elliya Siswanti; Syahfitri, Wilda Dani (Jurnal FARMASIMED (JFM), 2025)
The wound healing process is essential for restoring body tissue to its original integrity or normal function. This process involves several stages, including the inflammatory, proliferative, and maturation phases. Both internal and external factors play a role in accelerating wound healing. Kelakai leaves are traditionally used as a topical treatment for burns in gel form, as they are safe for use, non-toxic, and do not cause harmful side effects. The most significant effect was observed with the gel formulation containing 15% w/w kelakai leaf extract, which was able to reduce burn wound area by 13.75%. This demonstrates the effectiveness of kelakai leaf extract gel (Stenochlaena palustris (Burm. F.) Bedd.) in the wound healing process. Therefore, the gel has the potential to reduce the extent of burn injuries.The aim of this study was to analyze the effect of various concentrations of ethanol-based kelakai leaf extract gel. As an effort to reduce burn wound area, this research included several stages, starting from the collection of materials and equipment, plant identification, research procedures, to the extraction process of kelakai leaf simplicia using maceration. This was followed by phytochemical screening and gel formulation at concentrations of 5%, 10%, and 15%, which were then tested for effectiveness on male white rats. The data were analyzed using ANOVA with a significance level of p < 0.050. The findings indicate that the gel containing kelakai leaf extract has a significant effect in reducing the burn wound area in rats.